Feasibility of a Cognitive Behavioral Intervention to Manage Fatigue in Individuals With Traumatic Brain Injury: A Pilot Study. Issue 5 (September 2016) - Raina, Ketki D.; Morse, Jennifer Q.; Chisholm, Denise; Leibold, Mary Lou; Shen, Jennifer; Whyte, Ellen
Abstract : Objective: To evaluate the feasibility of conducting a randomized clinical trial of an Internet-based manualized intervention to teach individuals with traumatic brain injury to manage their fatigue. Setting: Community dwelling. Participants: Forty-one participants randomized to Maximizing Energy (MAX) intervention group ( n = 20) and Health Education group ( n = 21). Intervention: The experimental group (MAX intervention) received an 8-week program that combined education and Problem-Solving Therapy to teach individuals to manage fatigue-related problems. The attention control group received health education. Measures: Primary outcome measures pertained to the feasibility of conducting the trial. Secondary outcomes were fatigue impact and fatigue severity assessed at baseline and postintervention. Results: Of the 65 participants referred, 41 were enrolled (63% recruitment rate), of which 3 withdrew (92% retention rate). Participants in the experimental and control groups completed their homework 75% and 85% of the time, respectively, and were equally engaged in the sessions. Participants in the experimental group were able to learn and implement the MAX intervention steps. Effect sizes for all measures ranged from small (−0.17) to medium (−0.58) in favor of the intervention group. Conclusion: Findings from the study suggest that the MAX intervention is feasible to administer to individuals with post–traumatic brain injury fatigue.